1996
DOI: 10.1046/j.1525-1438.1996.06040323.x
|View full text |Cite
|
Sign up to set email alerts
|

A phase II study of ifosfamide and bleomycin in advanced or recurrent cervical carcinoma

Abstract: Harper PG. A phase II study of ifosfamide and bleomycin in advanced or recurrent cervical carcinoma. Int J Gynecol Cancer 1996; 6: 323-327.Thirty-seven patients with advanced or recurrent cervical squamous cell carcinoma were treated with ifosfamide 1.5 gm -2 on days 1-5 (with mesna as a uroprotector), and bleomycin 30 mg on day 1, every 3 weeks. A partial response rate of 21% (95%CI: 6-36%) was obtained in patients who had not received prior chemotherapy, with a median duration of response of 5 months. No com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Among 11 previously untreated patients with cervical cancer given full dose of bleomycin, two had SD, but nine patients had progressive disease on treatment (12) . In a recent phase II study of ifosfamide and bleomycin in cervical cancer, the results suggested that the addition of bleomycin only added to the toxicity without contribution to the activity of ifosfamide (13) . There is also no evidence that in neoadjuvant trials, the addition of bleomycin results in higher response rates (see Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Among 11 previously untreated patients with cervical cancer given full dose of bleomycin, two had SD, but nine patients had progressive disease on treatment (12) . In a recent phase II study of ifosfamide and bleomycin in cervical cancer, the results suggested that the addition of bleomycin only added to the toxicity without contribution to the activity of ifosfamide (13) . There is also no evidence that in neoadjuvant trials, the addition of bleomycin results in higher response rates (see Table 3).…”
Section: Discussionmentioning
confidence: 99%